Radiosensitivitas Kalus Embriogenik Kopi Robusta Bp 436 Terhadap Iradiasi Sinar Gamma - Ibrahim, Meynarti Sari Dewi; Randriani, Enny; Sari, Laela; Nuraini, Anne (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
High genetic diversity is one factor that determines the success of plant breeding. Mutation induction by gamma ray irradiation is one method to improve plant genetic diversity. This study aimed to 1) obtain growth regulators composition suitable in inducing embryogenic callus, 2) determine the effect of gamma ray irradiation on the growth and development of somatic embryos, and 3) obtain lethal dose (LD) 20 and 50 values in Robusta coffee BP 436. The study was conducted at the Tissue Culture Laboratory, Industrial and Beverage Crops Research Institute, from May 2017 to December 2018. Explants used were young leaves of Robusta coffee BP 436. Callus induction used ½ MS media with 2,4-D (4.52 μM) and 2-iP (0.00; 4.93; 9.86; 14.79; and 19.72 μM) treatment. Mutation induction was performed using gamma radiation dosed at 0, 10, 20, 30, 40, and 50 Gy treatments. The regeneration media was ½ MS containing GA3 (0 and 1 mg/l). The study used a complete randomized design with 10 replications. The results showed the best combination of plant growth regulator to induce the callus was 2.4-D 4.52 μM + 2-iP 19.72 μM. The fresh weight of cultures was inhibited above 30 Gy, whereas the number of somatic embryos decreased at doses above 10 Gy. Addition of GA3 1 mg/l in regeneration media increased the number of somatic embryos in torpedo phase, but not in gamma irradiation exposed calluses. The LD20 and LD50 of Robusta coffee BP 436 are 16.81 and 28.52 Gy, respectively.